Employee Performance is Reviewed from Work Environment, Work Discipline, and Work Performance - Yulianah Yulianah (Jurnal Mantik, 2022)
The purpose of this study is to see how work environment, discipline, and performance affect employee performance at PT.Mitra bisnis keluarga ventura. A sample of 30 respondents was used in the procedure. Quantitative data in the form of basic information was acquired by distributing questionnaires to PT.Mitra bisnis keluarga ventura staff on duty. The SmartPLS 3 application is used to process the data. The outer model, inner model, and hypothesis testing are the equation models studied. The results showed that the work environment and work performance proved to have a good impact on staff performance, while work discipline did not affect staff performance.